Low-dose prednisone chronotherapy for rheumatoid arthritis: a randomised clinical trial (CAPRA-2). Issue 2 (5th May 2012) - Buttgereit, Frank; Mehta, Daksha; Kirwan, John; Szechinski, Jacek; Boers, Maarten; Alten, Rieke E; Supronik, Jerzy; Szombati, Istvan; Romer, Ulrike; Witte, Stephan; Saag, Kenneth G
Abstract : Objective: To assess the efficacy and safety of low-dose prednisone chronotherapy using a new modified-release (MR) formulation for the treatment of rheumatoid arthritis (RA). Methods: In this 12-week, double-blind, placebo-controlled study, patients with active RA (n=350) were randomised 2:1 to receive MR prednisone 5 mg or placebo once daily in the evening in addition to their existing RA disease-modifying antirheumatic drug (DMARD) treatment. The primary end point was the percentage of patients achieving a 20% improvement in RA signs and symptoms according to American College of Rheumatology criteria (ie, an ACR20 response) at week 12. Changes in morning pain, duration of morning stiffness, 28-joint Disease Activity Score and health-related quality of life were also assessed. Results: MR prednisone plus DMARD treatment produced higher response rates for ACR20 (48% vs 29%, p<0.001) and ACR50 (22% vs 10%, p<0.006) and a greater median relative reduction from baseline in morning stiffness (55% vs 35%, p<0.002) at week 12 than placebo plus DMARD treatment. Significantly greater reductions in severity of RA (Disease Activity Score 28) (p<0.001) and fatigue (Functional Assessment of Chronic Illness Therapy-Fatigue score) (p=0.003) as well as a greater improvement in physical function (36-item Short-Form Health Survey score) (p<0.001) were seen at week 12 for MR prednisone versus placebo. The incidence of adverse events was similar for MR prednisone (43%) and placebo (49%). Conclusion: Low-dose MR prednisone added to existing DMARD treatment produced rapid and relevant improvements in RA signs and symptoms. ClinicalTrials.gov, number: NCT00650078